Availability and Usage of Laboratory Equipment for Chemistry Learning in Onitsha North Local Government Area - Chika Mary Ezeiheukwu (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Practical activities in Chemistry are vital for students' scientific skills, but the lack of laboratory equipment in Nigerian secondary schools hinders effective teaching and learning. Objective: This study investigated the availability and use of laboratory equipment for Chemistry learning in public secondary schools in Onitsha North, Anambra State, focusing on equipment availability and its usage during lessons. Methods: A descriptive survey research design was adopted. The sample consisted of 200 Chemistry students selected from 10 randomly chosen public secondary schools in the study area. Data were collected using a validated questionnaire with a reliability coefficient 0.72, determined using Cronbach's alpha. Data analysis was conducted using mean and standard deviation to answer three research questions. Results: The study revealed that laboratory equipment is not adequately available, and that the available laboratory equipment is poorly utilized in the learning of Chemistry in the selected schools. As a result, these students encounter difficulty in learning Chemistry, and lack the ability required to acquire scientific knowledge and skills. Conclusions: The study concluded that the limited availability and poor utilization of laboratory equipment negatively impact Chemistry's effective teaching and learning. Without sufficient resources, students are deprived of hands-on experiences vital for understanding scientific concepts. Contributions: This research highlights the infrastructure challenges public secondary schools face in practical science education, emphasizing the need for policymakers and educators to prioritize laboratory equipment and create an environment that supports students' scientific skill development.